2013
DOI: 10.1155/2013/692549
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Inhibits the Growth of Hepatocellular Carcinoma Independent of Angiogenesis

Abstract: Some sulphated polysaccharides can bind bFGF but are unable to present bFGF to its high-affinity receptors. Fucoidan, a sulphated polysaccharide purified from brown algae, which has been used as an anticancer drug in traditional Chinese medicine for hundreds of years, exhibits a variety of anticancer effects, including the induction of the apoptosis and autophagy of cancer cells, the inhibition of the growth of cancer cells, the induction of angiogenesis, and the improvement of antitumour immunity. Our researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…reported that fucoidan exhibited suppression of cell viability and proliferation of breast cancer cell lines . Fucoidan has also been reported to inhibit hepatoma tumor growth . Our results are consistent with those studies.…”
Section: Discussionsupporting
confidence: 93%
“…reported that fucoidan exhibited suppression of cell viability and proliferation of breast cancer cell lines . Fucoidan has also been reported to inhibit hepatoma tumor growth . Our results are consistent with those studies.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, it was found that VEGF secretion is increased during osteoblast differentiation, thus enhancing angiogenesis (Deckers et al, ). Although several studies have reported that treatment with fucoidan stimulates VEGF secretion, a certain study reported that fucoidan reduced expression and secretion of VEGF in retinal pigment epithelium cells (Dithmer et al, ), while Zhu, Cao, Zhang, Man, and Wu () reported that fucoidan did not affect the expression of VEGF in HCC cells. In contrast, the present study demonstrated that VEGF mRNA and protein levels were significantly increased during fucoidan‐induced osteoblast differentiation in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A family of sulfonated polysaccharides known as fucoidans have gathered increasing attention for their inherent biocompatibility and anti-inflammatory properties both in vitro and in vivo 11 . Importantly, several studies have also indicated the antimitogenic effects of fucoidans as they block cell cycle progression 12 , induce apoptosis and reduce tumorigenicity in several cancer cell lines 13 . However, the use of these biopolymers as a therapeutic is constrained by the high solubility of the polysaccharide chains, limiting their sustained functionality unless encapsulated in an external carrier 14 or presented on a two-M A N U S C R I P T …”
Section: Introductionmentioning
confidence: 99%